Ethical branding and marketing : cases and lessons - Gringarten, Hagai; Fernández-Calienes, Rául (Routledge advances in management and business studies., 2019)
Ethical Branding and Marketing: Cases and Lessons provides current perspectives on fascinating global cases focusing on the specific combination of the two fields of "ethics" and "branding," on their relationship, and on how that joint perspective shapes brands, companies, business strategies, and the market itself. In a contemporary environment of "truthiness" and fake news, it is more important than ever to review core principles of ethics and to reassess how these principles apply to today's branding and marketing practices. This book addresses practices in ethical branding and corporate culture. It includes such topics as truth, integrity, value, vulnerability, and differentiation. Collectively, these cases provide a contemporary overview of intriguing scenarios and best practices in ethical branding. The book provides the reader with real, updated insight into ethical decision making; helps students integrate ethics, branding strategy, and real life, complex situations into an effective learning process; and provides the reader with up-to-date ethical branding cases from around the world